2016
DOI: 10.1515/pjvs-2016-0096
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of different virulence grass carp reovirus strains in some neglected tissues

Abstract: Grass carp reovirus (GCRV) is the causative agent of hemorrhagic disease in infected grass carp. During an outbreak, a mortality rate of up to 85% can be experienced, thus leading to substantial economic losses.The current understanding of disease pathogenesis is limited, with the distribution and dynamics of replication amongst different GCRV strains in vivo largely unknown. We determined distribution of different GCRV strains in infected grass carp, especially in some neglected tissues, such as the gill, bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…This reversal may be a regulatory mechanism for recovery after viral infection. Another study on viral load of GCRV II-infected grass carp showed spleen and kidney were the tissues with the first increase in viral load and reached the peak of viral load on the 5th day, which may be due to the accumulation of virus caused by immune, hematopoietic, or glomerular filtration in these two tissues [16,17]. In studies of rare minnow infected with a virulent isolate of GCRV II, the spleen was also the tissue that reached the viral load peak relatively quickly [11].…”
Section: Apoptosis and Necroptosis-related Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…This reversal may be a regulatory mechanism for recovery after viral infection. Another study on viral load of GCRV II-infected grass carp showed spleen and kidney were the tissues with the first increase in viral load and reached the peak of viral load on the 5th day, which may be due to the accumulation of virus caused by immune, hematopoietic, or glomerular filtration in these two tissues [16,17]. In studies of rare minnow infected with a virulent isolate of GCRV II, the spleen was also the tissue that reached the viral load peak relatively quickly [11].…”
Section: Apoptosis and Necroptosis-related Pathwaysmentioning
confidence: 99%
“…The liver of teleosts serves as an important immune organ by housing numerous immune cell populations in addition to its functions in metabolism and the storing of nutrients [15]. Moreover, previous studies have shown that the liver and spleen are among the most severely infected tissues of grass carp and rare minnow [11,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…GCRV, the most pathogenic Aquareovirus, first isolated in China in 1983, was recognized by the International Committee on Taxonomy of Viruses (ICTV) as a species belonging to the genus Aquareovirus, AQRV-C (Zeng et al 2017). As a member of the family Reoviridae, GCRV is the causative agent of grass carp hemorrhage, which is the most severe viral disease in China (Liang et al 2016). The virion has a nonenveloped double capsid shell with an icosahedral morphological structure and consists of 11 segments of double stranded RNA (Tian et al 2013).…”
Section: Introductionmentioning
confidence: 99%